Tricuspid regurgitation is associated with increased mortality independent of pulmonary pressures and right heart failure: a systematic review and meta-analysis. (22nd October 2018) - Wang, Nelson; Fulcher, Jordan; Abeysuriya, Nishan; McGrady, Michele; Wilcox, Ian; Celermajer, David; Lal, Sean
Abstract: Aims: To undertake a systematic review and meta-analysis to determine the influence of tricuspid regurgitation (TR) severity on mortality. Methods and results: We performed a systematic search for studies reporting clinical outcomes of patients with TR. The primary endpoint was all-cause mortality and secondary endpoints were cardiac mortality and hospitalization for heart failure (HF). Overall risk ratios (RR) and 95% confidence intervals (CIs) were derived for each endpoint according to the severity of TR by meta-analysing the effect estimates of eligible studies. Seventy studies totalling 32 601 patients were included in the analysis, with a mean (±SD) follow-up of 3.2 ± 2.1 years. Moderate/severe TR was associated with a two-fold increased mortality risk compared to no/mild TR (RR 1.95, 95% CI 1.75–2.17). Moderate/severe TR remained associated with higher all-cause mortality among 13 studies which adjusted for systolic pulmonary arterial pressures (RR 1.85, 95% CI 1.44–2.39), and 15 studies, which adjusted for right ventricular (RV) dysfunction (RR 1.78, 95% CI 1.49–2.13). Moderate/severe TR was also associated with increased cardiac mortality (RR 2.56, 95% CI 1.84–3.55) and HF hospitalization (RR 1.73, 95% CI 1.14–2.62). Compared to patients with no TR, patients with mild, moderate, and severe TR had a progressively increased risk of all-cause mortality (RR 1.25, 1.61, and 3.44, respectively; P  < 0.001 for trend). Conclusions: Moderate/severe TR is associated with an increased mortality risk, which appears to be independent of pulmonary pressures and RV dysfunction. Abstract: